Implementation of Tax Hostage Taking (Gijzeling) in Indonesia in the Perspective of Tax Compliance and Deterrence Effect - Seselia Ongso; Sugeng Santoso PN (Green Publisher Indonesia, 2025)
Indonesia has reformed its tax system into a self-assessment framework that grants taxpayers the autonomy to independently calculate, report, and settle their tax obligations. However, this system faces significant enforcement challenges due to increasing tax arrears and low taxpayer compliance. When administrative instruments such as warning letters, forced collection notices, and asset confiscation prove ineffective, tax hostage-taking (Gijzeling) emerges as an ultimum remedium designed to create a deterrence effect. This study employs a normative legal method with conceptual and legislative approaches to analyze the effectiveness of tax hostage-taking from the perspectives of tax compliance and deterrence effect. Findings reveal that, theoretically, Gijzeling serves as a law enforcement instrument aimed at enhancing taxpayer compliance through criminal sanction threats that induce fear. However, empirical evidence demonstrates that tax hostage-taking has not effectively increased state revenue, as its deterrent impact is limited to directly affected taxpayers and fails to influence broader taxpayer behavior. Consequently, Gijzeling cannot serve as a primary strategy for improving tax compliance. Instead, sustainable compliance requires integrated approaches that strengthen voluntary compliance through enhanced literacy, transparency, and reconstruction of public trust.